Answer:
Choice A is correct answer.
Explanation:
We have given a quadratic equation.
11x²-4x =1
11x²-4x-1 = 0
ax²+bx+c = 0 is general quadratic equation.
Comparing above equations, we have
a = 11 , b = -4 and c = -1
x = (-b±√b²-4ac) / 2a is quadratic formula to solve equation.
Putting given values in above formula, we have
x = (-(-4)±√(-4)²-4(11)(-1) ) / 2(11)
x = (4±√16+44) / 22
x = (4±√60) / 22
x = (4±√4×15) / 22
x = (4±2√15) / 22
x= 2(2±√15) / 22
x = (2±√15) / 11
x = 2/11±√15/11 is solution of given equation.